Acute retinal necrosis (ARN) following chickenpox in a patient of Vogt-Koyanagi-Harada (VKH) syndrome using immunosuppressants. Issue 1 (28th November 2018) - Gupta, Rajan; Tyagi, Mudit; Balakrishnan, Divya; Rani, Padmaja Kumari
Abstract : A 36-year-old woman presented with diminution of vision and floaters in both the eyes. Both eyes had disc oedema, multiple pockets of neurosensory detachments along with vitritis. Fluorescein angiography and optical coherence tomography showed characteristic features of Vogt-Koyanagi-Harada (VKH) syndrome (figure 1 ). She was started on corticosteroid pulse therapy and immunosuppressants following which her VKH lesions resolved. However, she developed chickenpox after 2 weeks and after 1 month she developed discrete yellowish white retinitis patches in the periphery of the right eye which were consistent with a diagnosis of acute retinal necrosis. She was started on oral antivirals for the same and immunosuppressants were withheld in view of immunocompromised state potentially acting as a trigger for reactivation of latent virus. Retinitis patches started to resolve and showed a favourable response to the treatment.